Slang Words In Free Guy Movie By Matt Lieberman : Sociolinguistics Approach - Alya Namira; M. Kiki Wardana; Misla Geubrina (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2024)
This research looks into the different types of slang and the functions of the slang used in the Free Guy movie. The document analysis design was combined with descriptive qualitative research. In this study, the researcher applied Allan and Burridge (2006) theory to identify the types of slang and classify its functions. Technique of analyzing the data is by watching the movie and then transcribe the dialogue from movie. The data were taken from the texts and dialogues which contained slang words or phrases uttered by the characters of the Free Guy movie. According to the findings of this study, there were five types of slang used in the Free Guy movie. They were fresh and creative (48), flippant (15), imitative (12), acronym (4), and clipping (7). The type of fresh and creative dominates the slang words used in the Free Guy movie. Regarding slang's functions, this movie used slang in seven different ways. They were to address, to humiliate, to initiate relax conversation, to form intimate atmosphere, to express impression, to reveal anger and to show intimacy. In this movie, the function of slang that occurs most frequently is to initiate relax conversation.